Our migration story: history, the national curriculum, and re-narrating the British nation. Issue 18 (1st November 2021) - Lidher, Sundeep; McIntosh, Malachi; Alexander, Claire
ABSTRACT: This article explores schools as a key organisational context for the (re)production of national identity, and uses ongoing debates around the national curriculum for history, to illuminate the ongoing lacunae in Britain's national memory. Taking the recent Windrush scandal as a starting point, we examine how these events reflect broader processes of historical forgetting in contemporary discussions around migration, empire and its loss. While this has been challenged by academic historians, there is a significant gap between these discourses and how history is taught in schools, which remain a key site for the transmission of a highly selective historical narrative/repertoire. We use the experience of the recent Our Migration Story project to consider alternative ways of thinking about Britain's history, and to explore the importance of, and the difficulties in, challenging dominant memorialising practices.